Exploring consumer behaviour towards acceptance of Quick Response (QR) code Mobile Payment Systems (MPS) in Malaysia: application of Technology of Acceptance Model (TAM) - Nazri, Muhamad Azrin; Kamarudin, Nur Shuhada; MM, Agus Salim HR,SE.; Omar, Nor Asiah; Kamarubahrin, Aimi Fadzirul (Malaysian Consumer and Family Economics Association, 2024)
This study examines factors that influence the adoption of Quick Response code mobile payment systems. There is limited literature on mobile payment systems and their uptake, especially in developing nations, despite the growing interest in this system. This study looks at how consumers’ acceptance of the Quick Response code mobile payment system in Malaysia is influenced, primarily focusing on three components of the extended Technology Acceptance Model: perceived compatibility, perceived trust, and subjective norms. 457 questionnaires were analyzed using partial least squares structural equation modeling. It was found that the perceived usefulness, perceived ease of use, subjective norms, and perceived security of the Quick Response code payment have a significant impact on Malaysian consumers' intent to adopt the system. The findings offer insightful information on consumer behavior and beneficial recommendations for professionals and businesses. It also discusses the study's limitations and suggestions for future research.